Heterogeneity in bank responsiveness to policy and economic shocks: The role of capitalization - Gillian Kimundi (Kenya Bankers Association (KBA), 2024)
Capital is central to efficient intermediation and is a core indication of the financial health of a bank. Recent shifts in monetary policy, economic shocks and contextspecific events in interbank liquidity flow in Kenya call for a revisit of banks' response through the lens of their capitalization. Using data from 27 banks between 2001 and 2021, this study first reveals that there is heterogeneity in how banks respond to policy, economic and market shifts, and that capital plays a key role in maintaining (and in some cases amplifying) balance sheet activity and cushioning operating profitability. Small, lesser-capitalized banks are more sensitive to monetary policy and shifts in interbank market liquidity, whereas large, higher-capitalized banks are more sensitive to GDP shocks. Collectively, the role of capital depends on the nature of the shock, the size of the bank and the sub-period studied. The study concludes with relevant policy and bank-level implications from these findings.
Keywords: 330; Bankenliquidität; Schock; Geldpolitik; Wirkungsanalyse; Kenia